Implementasi Surat Keputusan Musyawarah No. 05 Tahun 2019: Studi Kasus Program Kerja Perkemahan Wirakarya Tahun 2020 di Kantor Kwartir Cabang Gerakan Pramuka Probolinggo - Marwiyah, Sitii; Rahmadi, Andhi Nur; Edy, Edy (Jurnal Sosial Humaniora Sigli, 2025)
This study aims to evaluate the implementation of the Decree of the Musyawarah No. 05 of 2019 related to the Work Program of the Wirakarya Camp in 2020 at the Probolinggo Branch of the Scout Movement. In this research, the methods applied include interviews with the management, program implementers, and Scout members, as well as analysis of relevant documents. The findings of this study indicate that the program has been implemented effectively, although there are several challenges related to coordination and communication among the management. The two main factors influencing the implementation of the program are the content of the policy and the context of implementation. This research also provides recommendations to enhance the program's effectiveness, including the need for training for the management and improvements in communication, as well as the provision of more adequate resources. It is hoped that the results of this study can have a positive impact on the development of the Scout Movement in Probolinggo.Keywords: Policy implementation, Scout Movement, Wirakarya Camp